2011
DOI: 10.1016/j.surg.2010.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Targeting gastrin-releasing peptide as a new approach to treat aggressive refractory neuroblastomas

Abstract: Background The overall survival for neuroblastoma remains dismal, largely in part, due to emergence of resistance to chemotherapeutic drugs. We have demonstrated that gastrin-releasing peptide (GRP), a gut peptide secreted by neuroblastoma, act as an autocrine growth factor. We hypothesized that knockdown of GRP will induce apoptosis in neuroblastoma cells to potentiate the cytotoxic effects of chemotherapeutic agents. Methods The human neuroblastoma cell lines (JF, SK-N-SH) were transfected with small inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…This suggested that GRP has a role in the proliferation and cell migration of human ovarian cancer cells. This finding is consistent with that of previous studies concerning other types of tumor (15)(16)(17)(18). Ischia et al (15) reported that GRP and GRPR are overexpressed in prostate cancer and can stimulate the growth of prostate cancer cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggested that GRP has a role in the proliferation and cell migration of human ovarian cancer cells. This finding is consistent with that of previous studies concerning other types of tumor (15)(16)(17)(18). Ischia et al (15) reported that GRP and GRPR are overexpressed in prostate cancer and can stimulate the growth of prostate cancer cells.…”
Section: Discussionsupporting
confidence: 92%
“…Ischia et al (15) reported that GRP and GRPR are overexpressed in prostate cancer and can stimulate the growth of prostate cancer cells. In addition, GRP was found to be associated with the migration and metastasis of cancer cells in neuroblastoma and breast cancer (16)(17)(18). It can therefore be concluded that GRP may be a potential novel target for the treatment of ovarian cancers.…”
Section: Discussionmentioning
confidence: 96%
“…We previously reported that GRP activated the PI3K/AKT signaling pathway to promote cell cycle progression in neuroblastoma cells [5], whereas, silencing GRP increased the expression of p21 in SK-N-SH cells [19]. In order to confirm the differential regulations of GRP-R signaling pathway on p21 and p27, we next examined the expressions of p21 and p27 using tetracycline-inducible GRP silencing in BE(2)-C cells.…”
Section: Resultsmentioning
confidence: 99%
“…Using our above mentioned metastasis model, we were able to demonstrate that targeting GRP inhibited tumor metastasis. Lack of complete inhibition of primary tumor growth could be potentially due to a marginal reduction of the proliferative capacity of neuroblastoma cells after GRP silencing [28]. The result of these in vivo experiments illustrates the inhibition of several key features in the invasion-metastasis cascade.…”
Section: Discussionmentioning
confidence: 86%